(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Electronic Tourism is characterized by its ability to manage the marketing based on a development and high sophisticated management to maximize profits, through the creation and strengthening the demand for tourism product, as well as increased competitiveness in the global tourism market, which opens the way for tourists to compare places and prices and promotions, and allow to the organizations of tourism in order to predict and targeting the consumer` s , and as a result the sales of e-tourism achieved 27% of the world’s total tourism sales in 2013. Through this research we focus on the significant role of e-tourism in the marketing of tourism services, as well as the study of the geographic distribution of sales for electronic tourism all over the world, and predict the future of e-tourism sales by the year 2018. finally , to identify the points of international tourism research trends .